Is Environmental Enrichment Ready for Clinical Application in Human Post-stroke Rehabilitation? - McDonald, Matthew W.; Hayward, Kathryn S.; Rosbergen, Ingrid C. M.; Jeffers, Matthew S.; Corbett, Dale (Frontiers in Behavioral Neuroscience, 2018)
Environmental enrichment has been widely used as a means to enhance brain plasticity mechanisms (e.g. increased dendritic branching, synaptogenesis, etc.) and improve behavioural function in both normal and brain-damaged animals. In spite of the demonstrated efficacy of environmental enrichment for enhancing brain plasticity it has largely remained a laboratory phenomenon with little translation to the clinical setting. Impediments to the implementation of enrichment as an intervention for human stroke rehabilitation and a lack of clinical translation can be attributed to a number of factors not limited to: i) concerns that environmental enrichment is actually the "normal state" for animals, whereas standard housing is a form of impoverishment, ii) difficulty in standardizing EE conditions across clinical sites, iii) the exact mechanisms underlying the beneficial actions of enrichment are largely correlative in nature, iv) a lack of knowledge concerning what aspects of enrichment (e.g. exercise, socialization, cognitive stimulation) represent the critical or active ingredients for enhancing brain plasticity, and v) the required "dose" of enrichment is unknown, since most laboratory studies employ continuous periods of enrichment, a condition that most clinicians view as impractical. In this review we summarize preclinical stroke recovery studies that have successfully utilized EE to promote functional recovery and highlight the potential underlying mechanisms. Subsequently, we discuss how EE is being applied in a clinical setting and address differences in preclinical and clinical EE work to date. It is argued that the best way forward is through the careful alignment of preclinical and clinical rehabilitation research. A combination of both approaches will allow research to fully address gaps in knowledge and facilitate the implementation of environmental enrichment to the clinical setting.